KNOWLEDGE RELATED TO STUDENTS READINESS TO FACE MENARCHE AT SDN KALIURIP PURWOREJO - Aldila Diah Rumiyandini; Zakiyatul Faizah; Irwanto Irwanto (UNIVERSITAS AIRLANGGA, 2021)
AbstractIntroduction : Menarche is the first occurrence of menstruation in the female. The more developing times, the age of menarche is getting earlier. Currently, the average teenage girls have menarche at 11 years old. With psychologically and emotionally unstable and insufficient knowledge of elementary school students, teenage girls are required to be ready for having menarche. Therefore, the readiness in facing menarche is essential to be studied to measure self-readiness if menarche suddenly comes to elementary school students. Furthermore, the knowledge factor, especially about menarche, is important to be conducted a measurement to find out whether there is a relation with readiness in facing menarche in students. Method: This study used an observational analytics method with a cross-sectional design. The number of samples was 53 students, and the sampling technique used the total sampling. The independent variable is knowledge, and the dependent variable is the readiness in facing menarche. This study was conducted on 4th-grade and 5th-grade students in SDN (State Elementary School) Kalurip Purworejo. The data collection technique of the study was conducted online using questionnaires, which were distributed in personal chat to the students and the students' guardians through the Google Form link. The data analysis used the chi-square test. Results: The results of the study show that students' knowledge is in the lack category (52.8%), and students are in the not ready category (62.3%) in facing menarche. The results of the chi-square test show the p-value of 0.000001 (p < 0.05). Conclusion: There is a relationship between knowledge and readiness in facing menarche. The less knowledge the more unprepared it is in facing menarche.